Coexistence of Umbilical Endometriosis and Sacrouterine Deep Endometriosis - Sutrisno; Tatit Nurseta; Ferdinand Umbu Pati (Asian Journal of Health Research, 2026)
Introduction: Endometriosis is a chronic gynecological condition affecting +10% of women of reproductive age, characterized by endometrial-like tissue outside the uterus causing pelvic pain, dysmenorrhea, and infertility due to inflammatory pathogenesis. While typically pelvic, rare extrapelvic manifestations like primary umbilical endometriosis present as painful umbilical nodules often mistaken for abscesses or hernias. This report aims to increase awareness of this uncommon condition to improve its recognition and management in clinical practice. Case Presentation: A 41-year-old woman presented with cyclical umbilical bleeding and a tender 2 cm umbilical mass, alongside longstanding dysmenorrhea since menarche. She had no prior surgeries or significant medical history. Ultrasound revealed a 3.75 cm ovarian endometrioma, leading to clinical diagnosis of umbilical and ovarian endometriosis. Laparoscopy confirmed umbilical endometriosis (Villar's nodule) with more extensive pelvic disease than anticipated, including uterosacral ligament lesions and suspected adenomyosis. The umbilical nodule and ovarian endometrioma were resected; histopathology confirmed ectopic endometrial tissue in all specimens. Postoperatively, she received six months of Leuprolide Acetate and remained asymptomatic at follow-up, with no recurrence at one-year evaluation. Conclusion: This report describes coexisting sacrouterine and umbilical endometriosis in a 41-year- old woman. Imaging and histopathology confirmed diagnosis after nonspecific symptoms. Surgical resection was performed. The umbilical nodule indicated more extensive pelvic disease, supporting theories of lymphovascular dissemination or metaplasia. This case highlights the need for clinical vigilance and comprehensive evaluation in endometriosis patients.